2007
DOI: 10.1002/pi.2325
|View full text |Cite
|
Sign up to set email alerts
|

Copolyester nanocomposites based on carbon nanotubes: reinforcement effect of carbon nanotubes on viscoelastic and dielectric properties of nanocomposites

Abstract: Nanocomposites based on an amorphous copolyester, poly(ethylene glycol-co-cyclohexane-1,4dimethanol terephthalate) and carbon nanotubes were fabricated using a simple melt processing technique. The reinforcement effect of carbon nanotubes in the copolyester was investigated experimentally using different approaches based on dynamic mechanical analysis, rheology and dielectric analysis. The nanocomposites show a mechanical reinforcement effect with significant increase in the stiffness especially in the rubbery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…However, when the GN content is over 1 wt%, the flow regime of PEEN/GN composites is significantly altered at low frequencies and a pseudo‐solid‐like behavior is more visible. This phenomenon has also been observed in both polymer/CNT and polymer/GN systems, and is mainly due to the existence of interactions between the fillers and polymer matrices , . With addition of more CNTs and GNs, however, the dependence on low frequency weakens and the slope of G ′ becomes flat.…”
Section: Resultsmentioning
confidence: 65%
See 3 more Smart Citations
“…However, when the GN content is over 1 wt%, the flow regime of PEEN/GN composites is significantly altered at low frequencies and a pseudo‐solid‐like behavior is more visible. This phenomenon has also been observed in both polymer/CNT and polymer/GN systems, and is mainly due to the existence of interactions between the fillers and polymer matrices , . With addition of more CNTs and GNs, however, the dependence on low frequency weakens and the slope of G ′ becomes flat.…”
Section: Resultsmentioning
confidence: 65%
“…Figure shows the complex viscosity (η*) of neat PEEN and PEEN composites with different nanocarbon contents. As can be seen in Figs (a) and (b), the η* of neat PEEN shows little frequency dependence and behaves almost like a Newtonian fluid, since the polymer chain is fully relaxed at all frequencies , . As the filler content increases, the slope of η* slightly increases, but a dramatic increase happens when CNTs are over 1 wt% or GNs are above 0.5 wt%.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…5 To date, nanocarbons of quasi-one-dimensional carbon nanotube (CNT) and two-dimensional graphene nanosheet (GN) have been mostly used to prepare polymer nanocomposites and their mechanical, thermal, electrical, morphological, especially dielectric, and rheological properties were studied. 8 On the contrary, zero-dimensional fullerene with a special hollow cage structure can be used to prepare low dielectric constant materials. In addition, the general results found that there is a dielectric transition regarding GN, which is usually larger than the rheological percolation threshold, but for CNT the dielectric transition has not been observed.…”
Section: Introductionmentioning
confidence: 99%